Practical implementation and validation of a functional testing model for early talent selection in wrestling - Patru, A. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2025)
Effective early talent identification in wrestling requires evidence-based tools that go beyond isolated motor tests and consider the complex interplay between physical, psychological, and sport-specific skills (Côté & Vierimaa, 2014; Malina, 2010). This study aimed to implement and validate a multidimensional testing model for children aged 6 to 10, with the purpose of supporting the early selection process in wrestling. The proposed battery included general motor assessments-such as coordination, balance, flexibility, and strength endurance-as well as wrestling-specific imitation exercises adapted from the initial technical-tactical curriculum for beginners (Bompa & Buzzichelli, 2018).